2021
DOI: 10.48550/arxiv.2109.05277
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improved DHOST Genesis

Mian Zhu,
Yunlong Zheng

Abstract: We improve the DHOST Genesis proposed in [1], such that the near scale invariant scalar power spectrum can be generated from the model itself, without invoking extra mechanism like a string gas. Besides, the superluminality problem of scalar perturbation plagued in [1] can be rescued by choosing proper DHOST action.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…The NEC is a fundamental principle in general relativity, stating that for any null vector, the contraction with the energy-momentum tensor yields a non-negative value. Nevertheless, scenarios that involve NEC violation have been conjectured to account for a range of early Universe phenomena, including the inflationary epoch and the genesis of primordial black holes [25][26][27][28][29][30][31][32]; see, for example, the review by [21]. Advances in modified gravity theories, especially within the framework of "beyond Horndeski" models [33][34][35][36][37][38][39], have shown that stable NEC violations are theoretically feasible, circumventing the issue of pathological instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…The NEC is a fundamental principle in general relativity, stating that for any null vector, the contraction with the energy-momentum tensor yields a non-negative value. Nevertheless, scenarios that involve NEC violation have been conjectured to account for a range of early Universe phenomena, including the inflationary epoch and the genesis of primordial black holes [25][26][27][28][29][30][31][32]; see, for example, the review by [21]. Advances in modified gravity theories, especially within the framework of "beyond Horndeski" models [33][34][35][36][37][38][39], have shown that stable NEC violations are theoretically feasible, circumventing the issue of pathological instabilities.…”
Section: Introductionmentioning
confidence: 99%